유아의 수면문제와 또래유능성 간의 관계에서 정서조절능력의 매개효과 - 박보경(Bokyung Park); 김민주(Minjoo Kim) (Korean Journal of child studies, 2022)
Objectives: This study investigated the relationship between preschoolers’ sleep problems, emotion regulation, and peer competence. Specifically, this study examined the mediating role of emotion regulation in the relationship between sleep problems and peer competence in preschoolers.Methods: The study group consisted of 194 preschoolers, aged 4-5 years (84 boys, 110 girls). Their mothers responded to questionnaires on their preschool children’s sleep problems, emotion regulation, and peer competence. Data were analyzed using frequency analysis, descriptive statistics, and correlation analysis with SPSS 22.0. PROCESS macro version 3.4 (Hayes, 2017) was used to analyze the mediating effect.Results: First, preschoolers’ sleep problems had a negative effect on peer competence when emotion regulation was not considered as a mediator; that is, preschoolers who experienced frequent sleep problems showed low peer competence. Second, preschoolers’ sleep problems did not directly affect peer competence when emotion regulation was considered as a mediator. Preschoolers’ sleep problems had only an indirect effect on peer competence through emotion regulation. That is, preschoolers who experienced many sleep problems did not control their emotions well, leading to low peer competence.Conclusion: This study confirmed the importance of sleep by revealing how preschoolers’ sleep problems influence their socioemotional development. The results of this study suggest that preschoolers should have sufficient, high-quality sleep to function better socially and emotionally. Health and parenting educators can utilize these findings in developing and implementing parent education programs that emphasize the importance of building healthy sleep habits for preschoolers. KCI Citation Count: 2